2002
DOI: 10.1006/mthe.2002.0676
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Delivery of a High-Capacity Adenoviral Vector Expressing Mouse CTLA4Ig Improves Skeletal Muscle Gene Therapy

Abstract: Adenoviral vectors (AdV) are promising vectors for gene transfer of skeletal muscle. To alleviate humoral and cellular immune responses that limit successful gene transfer, the present study determined the route of administration of AdmCTLA4Ig (an adenovirus that encodes a fusion protein of mouse cytotoxic T lymphocyte-associated protein 4 (CTLA4) and the Fc protion of immunoglobulin G (IgG), CTLA4Ig) that provided optimal AdV-mediated immunosuppression. AdmCTLA4Ig was administered either intramuscularly (i.m.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…This method was tested using two genes that block costimulatory signals that are required for an optimal immune response. 61,62 These authors report that the immunomodulatory genes CTLA4Ig and CD40Ig included in one HD vector and coadministered with an Ad vector coding for a reporter gene resulted in higher levels of transgene expression, lower levels of anti-Ad antibody and more prolonged transgene expression, when compared to controls. However, prolonged expression of these immunomodulatory genes compromised the host immune response.…”
Section: Readministration With Ad Vectors Remains a Challengementioning
confidence: 99%
“…This method was tested using two genes that block costimulatory signals that are required for an optimal immune response. 61,62 These authors report that the immunomodulatory genes CTLA4Ig and CD40Ig included in one HD vector and coadministered with an Ad vector coding for a reporter gene resulted in higher levels of transgene expression, lower levels of anti-Ad antibody and more prolonged transgene expression, when compared to controls. However, prolonged expression of these immunomodulatory genes compromised the host immune response.…”
Section: Readministration With Ad Vectors Remains a Challengementioning
confidence: 99%
“…Jiang and colleagues demonstrate that systemic delivery of cytotoxic T lymphocyte associated protein 4 and the Fc portion of immunoglobulin G (IgG) in adenoviral vectors, reduces the level of neutalising antibodies to AdV and enhanced Green Fluorescent Protein [67]. In these experiments sustained and stable transgene expression was noted for at least 2 months in muscle and expression was significantly higher than in controls.…”
Section: Immunosuppressionmentioning
confidence: 91%
“…Finally, blocking co-stimulatory pathways can be used to modulate the host adaptive immune response. Several groups showed that an antibody against CD40 ligand (Scaria et al, 1997;Wilson et al, 1998) or expressing CTLA4Ig, a fusion protein of cytotoxic T lymphocyteassociated protein 4 (CTLA4) and the Fc portion of immunoglobulin G (IgG), by the HD-Ad vector, improved transgene expression in rodents (Jiang et al, 2002;Yamashita et al, 2003).…”
Section: Adaptive Immune Responsementioning
confidence: 99%